Deep-Sourced Fluids From a Convergent Margin Host Distinct Subseafloor Microbial Communities That Change Upon Mud Flow Expulsion - Klasek, Scott A.; Torres, Marta E.; Loher, Markus; Bohrmann, Gerhard; Pape, Thomas; Colwell, Frederick S. (Frontiers in Microbiology, 2019)
Submarine mud volcanoes (MVs) along continental margins emit mud breccia and globally significant amounts of hydrocarbon-rich fluids from the subsurface, and host distinct chemosynthetic communities of microbes and macrofauna. Venere MV lies at 1600 m water depth in the Ionian Sea offshore Italy and is located in a forearc basin of the Calabrian accretionary prism. Porewaters of recently-extruded mud breccia flowing from its west summit are considerably fresher than seawater (10 PSU), high in Li+ and B (up to 300 and 8000 µM, respectively), and strongly depleted in K+ (<1 mM) at depths as shallow as 20 cm below seafloor. These properties document upward transport of fluids sourced from >3 km below seafloor. 16S rRNA gene and metagenomic sequencing were used to characterize microbial community composition and gene content within deep-sourced mud breccia flow deposits as they become exposed to seawater along a downslope transect of Venere MV. Summit samples showed consistency in microbial community composition. However, beta-diversity increased markedly in communities from downslope cores, which were dominated by methyl- and methanotrophic genera of Gammaproteobacteria. Sulfate and chloride concentrations were minor but significant contributors to variation in community composition. Metagenomic analyses revealed differences in relative abundances of predicted protein categories between Venere MV and other subsurface microbial communities, characterizing MVs as windows into distinct deep biosphere habitats.